Investigating the effects of dimension-specific sentiments on product sales: The perspective of sentiment preferences - JIANG, Cuiqing (Institutional Knowledge at Singapore Management University, 2021)
While literature has reached a consensus on the awareness effect of online word-of-mouth (eWOM), this paper studies its persuasive effect, specifically, the dimension-specific sentiment effects on product sales. We allow the sentiment information in eWOM along different product dimensions to have different persuasive effects on consumers’ purchase decisions. This occurs because of consumers’ sentiment preference, which is defined as the relative importance consumers place on various dimension-specific sentiments. We use an aspect-level sentiment analysis to derive the dimension-specific sentiments and PVAR (panel vector auto-regression) models to estimate their effects on product sales using a movie panel dataset. The findings show that three dimension-specific sentiments (star, genre and plot) are positively related to movie sales. Regarding consumers’ sentiment preferences, we find that the positive relationship with movie sales is stronger for plot sentiment relative to star sentiment for low-budget movies, whereas the positive relationship with movie sales is stronger for star sentiment relative to plot and genre sentiments for high-budget movies.